Talking in a language that everyone can understand? Transparency of speeches by the ECB Executive Board - Alexander Glas; Lena Müller (Friedrich-Alexander-Universität Erlangen-Nürnberg, Institute for Economics, 2021)
Using novel data on speeches held by members of the European Central Bank's Executive Board, we investigate whether monetary policy transparency has increased over time. With respect to the general public as the target audience, our findings suggest that the European Central Bank successfully improved the frequency and clarity of information provision since its inception. The increase in transparency is gradual, rather than being induced by changes in the Executive Board's composition or major economic events such as the Great Recession. However, the clarity of speeches in recent years is still fairly low. Moreover, our findings indicate that clarity decreased under Christine Lagarde's presidency following the outbreak of the Coronavirus pandemic. We conclude that while the European Central Bank was able to increase transparency over time, further improvements in clarity are required to make monetary policy truly accessible to the broad public.
Keywords: E52; E58; 330; Central Bank Communication; Monetary Policy Transparency; Clarity; Readability